DIGITAL INTEGRATION OF FINANCIAL AND MANAGEMENT REPORTING IN THE INTERESTS OF STAKEHOLDERS - Shkromyda , V.V.; Maksymiv , Yu.V.; Gnatyuk, T.M. (The actual problems of regional economy development, 2025)
The article reveals approaches to the digital integration of financial and management reporting in the context of growing stakeholder information. The article reveals approaches to the digital integration of financial and management reporting in the context of growing stakeholder information requests. It is proven that the traditional distinction between financial and management reporting does not allow to fully provision of relevant, holistic, and analytically rich information necessary for making informed management decisions and ensuring business transparency. The need to form a single accounting and analytical space in which financial and management information are consistent and complement each other is substantiated. It is proposed to develop the domestic accounting chart of accounts, in particular by expanding the functional purpose of class 8 in the direction of detailing and analytics. It is proposed that the vertical integration of financial and management accounting accounts be implemented by opening various types of analytical sub-accounts of a lower order to synthetic accounts in accordance with the information needs of business management. In turn, horizontal integration of accounts is recommended to be implemented by forming correspondences of accounts of classes 1-7 and 9 of financial accounting and accounts of class 8 intended for management accounting needs. This approach will allow generating the necessary information accordingly for specific target requests of business management and its key stakeholders. The combination of financial and management accounting accounts in the conditions of vertical and/or horizontal integration is characterized by positive features, since it allows for implementation in the activities of various economic entities and for any information needs of management, as well as the possibility of automating accounting processes using specialized software technologies, which prevents the increase in the labor intensity of accounting work. In this context, the role of digital technologies in implementing the process of integrating types of reporting, increasing the reliability of information, automating accounting procedures, and adapting reporting data to the requirements of different user groups is highlighted. The advantages of digital reporting integration to ensure sustainable development, effective communication with stakeholders, and improved the quality of management decisions are summarized.